PENGARUH KUALITAS AUDIT INTERNAL PADA EFEKTIVITAS PENGENDALIAN INTERNAL KOPERASI SERBA USAHA - Savitri, Dewa Ayu Mellyananda; Suryanawa, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Internal control structure (SPI) as a type of supervision is needed because it covers a very broad range of policies and procedures and can cover various organizational goals. Internal control in cooperatives is supervisors or parties who are given the authority and responsibility to carry out supervision and inspection in cooperatives. The purpose of this study was to analyze the effect of the quality of internal audit on the effectiveness of the internal control of multipurpose cooperatives in Gianyar Regency. Data was collected by distributing questionnaires to 156 multi-business cooperatives in Gianyar Regency. The method of determining the sample used is purposive sampling, in order to obtain 156 samples with 312 people as respondents in this study. Technical analysis used to test the hypothesis is simple linear regression analysis. The results of the analysis in this study indicate that audit quality has a positive effect on the effectiveness of the cooperative's internal control